Jewish Solicitory Poetry in the Eighteenth-Century Russian Empire: Materiality, Poetics, Diplomacy - Averbuch, Alex (AJS review, 2025)
This article provides a transdisciplinary analysis of solicitory Hebrew panegyrics composed in the late eighteenth century to aesthetically articulate political, social, and economic aspirations of Jews in the Russian Empire to Catherine II. It shows that the poetic solicitations, enhanced with distinct decorative features and presented at pomp-filled ceremonies, had a theurgical aesthetic effect, making positive outcomes more likely. Toward this end, the article discloses the poems' material, visual, and textual aspects, highlighting their ornamentation, length, and the quality of their material, and suggesting that they were prized not only as cultural capital, but also as luxury goods with tangible characteristics., Abstract:, This article provides a transdisciplinary analysis of solicitory Hebrew panegyrics composed in the late eighteenth century to aesthetically articulate political, social, and economic aspirations of Jews in the Russian Empire to Catherine II. It shows that the poetic solicitations, enhanced with distinct decorative features and presented at pomp-filled ceremonies, had a theurgical aesthetic effect, making positive outcomes more likely. Toward this end, the article discloses the poems' material, visual, and textual aspects, highlighting their ornamentation, length, and the quality of their material, and suggesting that they were prized not only as cultural capital, but also as luxury goods with tangible characteristics.